2014
DOI: 10.1371/journal.pone.0105286
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Antrodia camphorata Extracts against Oral Bacteria

Abstract: Antrodia camphorata (A. camphorata) is a unique, endemic and extremely rare mushroom species native to Taiwan, and both crude extracts of and purified chemical compounds from A. camphorata have been reported to have a variety of significant beneficial effects, such as anti-tumor and anti-inflammatory activity. However, reports on the effects of A. camphorata against dental pathogens have been limited. Oral health is now recognized as important for overall general health, including conditions such as dental car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…As observed from the results, Soy BA resulted in elevated levels of the decanoic fractions, the synergistic effect resulted in the release of these antimicrobial fractions, owing to the action of the b-glucosidase from Bacillus (Wei et al, 2008) and the invertase, amylase, and cellulases from Aspergillus. (Ghannoum, Thomson, Beadle, & Bowman, 1988;Lien et al, 2014;Morris, Kheltry, & Seitz, 1978;Peterson, 2013;Sirdaarta & Cock, 2008;Tomassi et al, 2008). Soy A ( Figure 8a) and Soy BA (Figure 8c) were observed to contain Galactofuran (34.030, 34.035) compounds, we also observe Xylitol and furan derivatives in the Soy AB extracts too.…”
Section: Gc-ms Analysis Of Extracts For Antimicrobial Compoundsmentioning
confidence: 58%
See 1 more Smart Citation
“…As observed from the results, Soy BA resulted in elevated levels of the decanoic fractions, the synergistic effect resulted in the release of these antimicrobial fractions, owing to the action of the b-glucosidase from Bacillus (Wei et al, 2008) and the invertase, amylase, and cellulases from Aspergillus. (Ghannoum, Thomson, Beadle, & Bowman, 1988;Lien et al, 2014;Morris, Kheltry, & Seitz, 1978;Peterson, 2013;Sirdaarta & Cock, 2008;Tomassi et al, 2008). Soy A ( Figure 8a) and Soy BA (Figure 8c) were observed to contain Galactofuran (34.030, 34.035) compounds, we also observe Xylitol and furan derivatives in the Soy AB extracts too.…”
Section: Gc-ms Analysis Of Extracts For Antimicrobial Compoundsmentioning
confidence: 58%
“…Figure a–c gives the spectra obtained from Soy A (a), Soy AB (b), and Soy BA(c) water extracts in ethanol. As observed from http://onlinelibrary.wiley.com/doi/10.1111/jfpp.13412/suppinfo, the compounds marked in bold are those known to possess antibacterial activity, mostly those of butane (20.966, 21.063, 26.740, 26.865) and furan (26.865, 34.030, 34.035, 36.823, 38.778) derivatives and xylitol (36.133) (Ghannoum, Thomson, Beadle, & Bowman, ; Lien et al, ; Morris, Kheltry, & Seitz, ; Peterson, ; Sirdaarta & Cock, ; Tomassi et al, ). Soy A (Figure a) and Soy BA (Figure c) were observed to contain Galactofuran (34.030, 34.035) compounds, we also observe Xylitol and furan derivatives in the Soy AB extracts too.…”
Section: Resultsmentioning
confidence: 98%
“…Previous studies have shown that AC extracts have antibacterial and antiviral properties [ 16 , 17 , 18 ]. Therefore, the effect of ACEW diet supplementation on the inhibition of microbial growth in water was examined.…”
Section: Resultsmentioning
confidence: 99%
“…Many plant extracts including plant essential oils have been reported to have potential inhibitory effects against many strains of Gram-negative and Gram-positive pathogenic bacteria (5)(6)(7). The in vitro inhibition of some oral bacteria by the extracts of Antrodia camphorate (8) and Prunus mume (9) has been reported. However, there are still few reports of plant extracts on the inhibitory effects against oral pathogens.…”
Section: Discussionmentioning
confidence: 99%